2016
DOI: 10.3389/fmed.2016.00051
|View full text |Cite
|
Sign up to set email alerts
|

TP53 Gene Status Affects Survival in Advanced Mycosis Fungoides

Abstract: TP53 is frequently mutated in different types of neoplasms including leukemia and lymphomas. Mutations of TP53 have also been reported in mycosis fungoides (MF), the most common type of cutaneous lymphoma. However, little is known about the frequency, spectrum of mutations, and their prognostic significance in MF. In this study, we have optimized the protocol for Sanger sequencing of TP53 using DNA extracted from archival paraffin-embedded biopsies. Of 19 samples from patients with stage IIB MF or higher, 31% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…TP53 mutations were previously reported to occur in advanced disease stages and were associated with poor survival in patients [ 51 ]. Hence, we performed the sequencing of the TP53 gene and identified that Sézary cells Hut78 and SeAx carry mutations of p53 (Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…TP53 mutations were previously reported to occur in advanced disease stages and were associated with poor survival in patients [ 51 ]. Hence, we performed the sequencing of the TP53 gene and identified that Sézary cells Hut78 and SeAx carry mutations of p53 (Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…It is often referred to as the “guardian of the genome” as p53 modulates the cell cycle and initiates apoptosis in response to DNA damage . Numerous studies have examined the relationship between p53 and mycosis fungoides with respect to disease progression, prognosis, and large cell transformation, although the results are not always consistent . With the benefit of being a large tertiary referral center with an expert cutaneous lymphoma clinic with extensive clinical annotation, we aim to explore whether p53 and Ki‐67 immunohistochemistry can be useful and readily available ancillary studies to promote accurate diagnosis of large cell transformation in mycosis fungoides.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 Numerous studies have examined the relationship between p53 and mycosis fungoides with respect to disease progression, prognosis, and large cell transformation, although the results are not always consistent. [20][21][22][23] With the benefit of being a large tertiary referral center with an expert cutaneous lymphoma clinic with extensive clinical annotation, we aim…”
Section: Introductionmentioning
confidence: 99%
“…2 The identification of those patients likely to progress remains a challenge. [3][4][5][6] Neoplastic T lymphocytes evade apoptotic stimuli, resulting in frequent failure of therapeutic treatment. [7][8][9][10][11] In the last decade, among several signalling pathways reported to be deregulated in CTCL, [12][13][14][15] including PI3K/AKT, JAK/STAT, 16,17 RAS and nuclear factorkappa B (NF-jB) pathways, a major role has been attributed to the persistent activation of NF-jB in chemoresistance of MF malignant cells.…”
Section: Introductionmentioning
confidence: 99%